Synergistic Effects of Nanocomposite Films Containing Essential Oil Nanoemulsions in Combination with Ionizing Radiation for Control of Rice Weevil Sitophilus oryzae in Stored Grains. Issue 6 (20th May 2019) - Hossain, Farah; Follett, Peter; Salmieri, Stephane; Vu, Khang Dang; Harich, Mehdi; Lacroix, Monique
Abstract : Abstract: The fumigant toxicity of eight individual essential oils (EOs; basil, cinnamon, eucalyptus, mandarin, oregano, peppermint, tea tree, and thyme) and one binary combination (thyme and oregano) for control of the rice weevil, Sitophilus oryzae, were investigated. In bioassays, all individual and combined EOs were toxic to the rice weevil. Eucalyptus EO exhibited the highest toxicity among the individual EO treatments, causing 100% mortality at a minimum concentration of 0.8 µL/mL after 24 hr of exposure. The combination treatment of oregano and thyme EO displayed higher fumigant activity than the individual oregano or thyme treatments. A stable oil‐in‐water nanoemulsion was evaluated using high‐pressure homogenization (microfluidization [MF]) and varying the pressure and number of cycles. The droplet size of the emulsions was found to decrease from 217 to 71 nm and encapsulation efficiency increased from 37% to 84% with increasing MF pressure and number of cycles. The optimum conditions for preparing the mixture of oregano and thyme EO nanoemulsions were evaluated to be homogenization pressure of 103 MPa and three cycles. Incorporating an oregano:thyme nanoemulsion (0.75%) into cellulose nanocrystal (CNC) containing chitosan (CH/CNC), methyl cellulose (MC/CNC), and polylactic acid (PLA/CNC) composite films resulted in extended diffusion matrices causing 32% to 51% rice weevil mortality after 14 days exposure. Irradiation at 200 Gray alone caused 79% mortality and increased to 100% when combined with the bioactive chitosan film containing the oregano:thyme nanoemulsion. Practical Application: A binary combination of oregano:thyme has potential as a biopesticide against stored product pests. The encapsulation of EO nanoemulsions into biopolymeric support could be used for bioactive packaging to prevent food spoilage and extend shelf life. Combining bioactive films with irradiation can provide complete control of rice weevil in packaged rice. The system developed in this research may also be extended to explore other food‐packaging films with various food models to control different types of stored pests.